The dynamics of compliance with the national core standards for health establishments in South Africa: a case study of two tertiary hospitals in Gauteng province - Mabena, Sphiwe Yomvula (My University, 2022)
South Africa has made efforts to improve quality within the healthcare institutions by formulating policies and implementing strategies that are intended to improve health outcomes and strengthen the health system. The National Department of Health (NDoH) developed National Core Standards (NCS) which are intended to set the benchmark for quality care against which delivery of services at all health facilities can be monitored (NDoH, 2011). In order to focus attention on the implementation of the NCS, the department of health selected six key priority areas (KPAs) which health care institutions are required to comply with to fast track quality improvement. Audits have shown marked differences in terms of compliance to these NCS and the KPA’s between hospitals classified in the same categories as one another and therefore, ostensibly having access to similar resources. This study was conducted at two tertiary hospitals in Gauteng – the one that achieved the highest level of compliance in an audit and the one that achieved the lowest level of compliance in an attempt to understand the dynamics that influence compliance and therefore make recommendations to improve compliance. An exploratory case study method was used with multiple methods of data collection. This included a document review of the DoH policies and other related documents related to compliance to the NCS; semi structured interviews of staff members in the two selected hospitals solicit views and opinions about the process of the implementation of the six KPAs of the NCS and a qualitative social network analysis (SNA) to explore the relationships and connections between the actors responsible for the implementation of the NCS in the two tertiary hospitals in Gauteng using “net-map” tools. Integration of all three phases of the study was done using Walt and Gilson’s policy framework (1994) to develop actionable recommendations to improve the implementation of the six KPAs of the NCS in the best and worst performing hospitals in Gauteng province. The results of the study showed that design of the assessment tool, structural issues at the hospitals, leadership and governance, human resource allocation, training and procurement of goods and services all had impact on the implementation of the NCS and related policies. It was clear from the findings of this study that there were overlapping elements in the provision and implementation of the NCS policy. It was clear from this study, and many other studies, that policy in itself cannot resolve the problems in the health services and can also not improve quality of care unless it is implemented within a well-planned national strategy to address many issues hampering its implementation.
A thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2022